1983
DOI: 10.1111/j.1748-1716.1983.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

An oscillating intratubular pressure response to alterations in Henle loop flow in the rat kidney

Abstract: We describe in gas anesthetized rats an oscillating intratubular pressure response, probably of vascular origin, sensitive to small physiological changes in fluid delivery to the distal tubule. The oscillation apparently indicates that an adjustment of vascular resistance is in operation, but at present it reveals neither the effector site (afferent and/or efferent arteriole) nor the effector mechanism (vasoconstriction and/or dilatation). The renin-angiotensin system seems to be involved in this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 13 publications
5
60
0
Order By: Relevance
“…5 In these studies, we found that activation of the calcium-sensing receptor produced increases in Ca Interestingly, the frequency of oscillations in perimacular cTAL cell [Ca 2ϩ ] i is remarkably close to that of TGF-dependent oscillations in tubular fluid flow and renal blood flow in anesthetized animals. [12][13][14][15][16][17] We do not have evidence that the increases in DT [Ca 2ϩ ] i contributed to or were associated with the activation of afferent arteriole smooth muscle cell [Ca 2ϩ ] I ; however, these new findings are at least suggestive and should stimulate future research efforts in understanding communication processes between tubule and glomerular structures.…”
Section: Discussionmentioning
confidence: 95%
“…5 In these studies, we found that activation of the calcium-sensing receptor produced increases in Ca Interestingly, the frequency of oscillations in perimacular cTAL cell [Ca 2ϩ ] i is remarkably close to that of TGF-dependent oscillations in tubular fluid flow and renal blood flow in anesthetized animals. [12][13][14][15][16][17] We do not have evidence that the increases in DT [Ca 2ϩ ] i contributed to or were associated with the activation of afferent arteriole smooth muscle cell [Ca 2ϩ ] I ; however, these new findings are at least suggestive and should stimulate future research efforts in understanding communication processes between tubule and glomerular structures.…”
Section: Discussionmentioning
confidence: 95%
“…However, in the mid-1980s, experiments by Leyssac and Baumbach 11 and by Holstein-Rathlou and Leyssac 12 demonstrated that the TGF regulation in rat nephrons tends to be unstable and to generate self-sustained oscillations in the tubular pressures and flows with a typical period of 30-40 s. While for normal rats the oscillations had the appearance of a regular self-sustained oscillation with a sharply peaked power spectrum, highly irregular oscillations, displaying a broadband spectral distribution with strong subharmonic components, were observed for spontaneously hypertensive rats. It has subsequently been found that irregular oscillations can be elicited for rats with normal blood pressure, provided that the arterial blood pressure is increased by reducing the blood flow to the other kidney ͑two-kidney, one-clip Goldblatt hypertensive rats͒.…”
Section: Pressure and Flow Control In The Kidneymentioning
confidence: 99%
“…Early experiments by Leyssac and Baumbach 8 and by Leyssac and Holstein-Rathlou 9,10 demonstrated that the feedback regulation could become unstable and generate selfsustained oscillations in the proximal intratubular pressure with characteristic periods of 30-40 s. While for normal rats the oscillations had the typical appearance of a limit cycle, highly irregular oscillations were found for spontaneously hypertensive rats ͑SHR͒. Oscillations were observed for 50%-80% of the investigated nephrons.…”
Section: Introductionmentioning
confidence: 99%